An approach to environmental sensitivity index study at coastal area toward oil spill accident: A case study on the northern and southern coast of Madura Island. Issue 1 (January 2020) - Rustandi, Y; Damar, A; Fahrudin, A; Rakasiwi, G; Affandy, A; Hamdani, A; Mulyana, D; Kamsari,
Abstract: Coastal resources and their local community economic activities are prone to oil spills pollution from tanker accidents or unappropriated operational procedures from the oil and gas industry. This study was aimed to develop supporting a prevention strategy to minimize damage and to ensure vulnerable natural resources and the local community in coastal areas are protected. Two methodologies applied to perform an integrated Environmental Sensitivity Index (ESI) named IPIECA (International Petroleum Industry Environmental Conservation Association) method and methodology that was developed by an expert from the Center of Coastal and Marine Resources Studies, IPB University (CESI, Composite ESI). The area study was located in the coastal area of Madura Island, East Java Province. Various ecosystems, shoreline types, and coastal area utilizing types have resulted in many combinations of ESI. The highest level of sensitivity will be prompted by the existence of an important ecosystem and economically land use utilizing. The important ecosystems, such as mangrove ecosystems, will result in more sensitive areas in IPIECA criteria than in CESI criteria. Consistently, in terms of socio-economic activities, land use, which has high production value and a high amount of persons employed, will be categorized as a very sensitive area.